Implantable Cardioverter-Defibrillator of Korean Patients in a Single Center Registry - Hwang, Jin Kyung; Gwag, Hye Bin; Park, Seung-Jung; Park, Kyoung-min; Kim, June Soo; On, Young Keun (International journal of arrhythmia, 2017)
Background and Objectives: The safety and efficacy of implantable cardioverter-defibrillator (ICD) for Korean is unclear. We investigated the clinical characteristics and outcomes of Korean patients undergoing ICD for primary or secondary prevention. Materials and Methods: From October 1999 to December 2016, 396 cases (365 patients) of ICD implantation were performed: Baseline characteristics, procedural findings, and clinical outcome data were collected retrospectively from our ICD registry. The primary outcome was composite of cardiac death, appropriate shock or antitachycardia pacing. Results: Among 365 patients, 91 patients (25.9%) had ICD for primary prevention and 274 patients (75.1%) were for secondary prevention (51.2±17.10 years, male was 80.8%). The median follow-up period was 3.1 years (interquartile range: 1.6–6.0 days). The most prevalent etiology was dilated cardiomyopathy (46.2%) in the primary prevention and idiopathic ventricular tachycardia or fibrillation (24.4%) in the secondary prevention. The primary outcome was noted in 28.6% of the primary prevention and 33.2% of the secondary prevention (P=0.44). The rate of cardiac death was 2.2% in the primary prevention and 1.8% in the secondary prevention (P=1.00). The hospitalization due to heart failure was higher in the primary prevention compared with the secondary prevention (23.1% versus 13.5%, P=0.03). ICD therapy occurred in 134 patients (36.7%). Among them, 60 patients (44.8% of ICD therapy) experienced inappropriate shock. The most common cause of inappropriate shock was atrial fibrillation of flutter (AF/AFL). Conclusion: The clinical efficacy and safety of ICD in Korean is consistent with the data from Western countries. KCI Citation Count: 0